Sponge-dwelling snapping shrimps (Alpheidae: Synalpheus) of Barbados, West Indies, with a description of a new eusocial species - Hultgren, Kristin M.; Macdonald Iii, Kenneth S; Duffy, J. Emmett (Zootaxa, 2011)
Sampling of eight sites along the west coast of Barbados, West Indies, yielded 14 species of sponge-dwelling shrimps in the gambarelloides group of the genus Synalpheus, including one new species described here as Synalpheus microneptunus n. sp. The new species is a member of the S. paraneptunus Coutière species complex and is distinguished from other species in that group by the combination of four carpal segments in the second pereopod, uropodal exopod with 2 nd distolateral tooth smaller than the other two teeth and set in line with movable spine, and a small blade on the scaphocerite. Synalpheus microneptunus n. sp. is the smallest species in the complex (2.2-2.9 mm CL) and lives in small colonies, usually with fewer than 10 individuals, often with a single breeding female. Synalpheus thele Macdonald, Hultgren & Duffy is reported for the first time from outside its type locality in Jamaica. Sampling in Barbados produced fewer species than did similar efforts in Jamaica and Curaçao, possibly due to the relatively isolated position of the island at the eastern (windward) edge of the Caribbean Sea.